Intermediating Role of Human Resource Management in Organizational Conflict and its influence on Organizational Effectiveness–Evidence from Bangladesh’s Banking Sector (American Journal of Economics and Business Innovation, 2022)
Since the economy has changed due to globalization, markets have become extremely competitive. The market system is shaping the expansion of business, the economy, and other areas. As a result, human resource management (HRM) plays a crucial function. The study’s goal is to assess the effectiveness of human resource management (HRM) and how organizational disputes affect HRM’s influence on organizational effectiveness in Bangladesh’s banking industry. This paper used primary data from 400 employees in Bangladesh’s banking industry through a questionnaire, of which 310 were returned for the purpose of testing study hypotheses. PLS-SEM has been used for data analysis and the result shows that the functional conflict has a favorable link to organizational success. Additionally, it has been discovered that HRM practices have a substantial impact on organizational effectiveness and can change dysfunctional conflict into functional conflict. The finding in this study reveals that there is a strong correlation between dysfunctional conflict and organizational success. This paper provides administrators in Bangladesh’s banking sector with an essential framework for comprehending why HRM is important in banks and other enterprises and demonstrates a positive association between HRM performance and organizational success.